2022
DOI: 10.1021/acsomega.1c06699
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Rigidity of Kinesin-Propelled Microtubules in an In Vitro Gliding Assay Using the Deep-Sea Osmolyte Trimethylamine N-Oxide

Abstract: The biomolecular motor protein kinesin and its associated filamentous protein microtubule have been finding important nanotechnological applications in the recent years. Rigidity of the microtubules, which are propelled by kinesin motors in an in vitro gliding assay, is an important metric that determines the success of utilization of microtubules and kinesins in various applications, such as transportation, sensing, sorting, molecular robotics, etc. Therefore, regulating the rigidity of kinesin-propelled micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This feature can provide additional and potentially orthogonal angles when looking at biological systems, whether one is trying to understand and describe them, 9,[106][107][108][109][110][111][112][113][114] monitor or regulate them in vitro and in vivo, [115][116][117][118][119][120] replicate and mimic them ex vivo or "on-achip", [121][122][123][124][125] or model them in silico. [126][127][128][129] On top of that, these novel DESs are also bioinspired engineered media which may serve as new tools and open up new opportunities for action in diagnosis, monitoring, treatment and manufacture across several research fields and market sectors, 9,130,[131][132][133][134][135][136][137][138][139][140][141][142][143] starting from applications and current use cases where single osmolytes or aqueous mixtures have shown promise 144 (Fig. 5).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature can provide additional and potentially orthogonal angles when looking at biological systems, whether one is trying to understand and describe them, 9,[106][107][108][109][110][111][112][113][114] monitor or regulate them in vitro and in vivo, [115][116][117][118][119][120] replicate and mimic them ex vivo or "on-achip", [121][122][123][124][125] or model them in silico. [126][127][128][129] On top of that, these novel DESs are also bioinspired engineered media which may serve as new tools and open up new opportunities for action in diagnosis, monitoring, treatment and manufacture across several research fields and market sectors, 9,130,[131][132][133][134][135][136][137][138][139][140][141][142][143] starting from applications and current use cases where single osmolytes or aqueous mixtures have shown promise 144 (Fig. 5).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…On top of that, these novel DESs are also bioinspired engineered media which may serve as new tools and open up new opportunities for action in diagnosis, monitoring, treatment and manufacture across several research fields and market sectors, 9,130,131–138,139–143 starting from applications and current use cases where single osmolytes or aqueous mixtures have shown promise 144 (Fig. 5).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…33,34 Recent studies have also identified glycine and betaine as cryoprotective osmolytes, providing nontoxic alternatives to conventional cryoprotecting agents and meeting the increasing demand in modern cell-based medicine. 10 Osmolytes have potential applications in the food industry, 41 fermentability prediction, biotechnology, 43 and more.…”
Section: Osmolytesmentioning
confidence: 99%
“…Osmolytes also find wide application in other fields. Ectoine, a widespread osmolyte used by halophilic bacteria to combat high osmotic stress, can be directly and efficiently applied in various functionalities ranging from cosmetics to therapeutic agents. TMAO has been employed for reversible modulation of kinesin-propelled microtubules, enabling applications in transportation, sensing, sorting, molecular robotics, and more . In addition to direct use, osmolytes can be encapsulated by suitable nanomaterials and successfully delivered within cells for cryopreservation or specific therapeutic purposes. , Trehalose, for example, has been extensively explored as an alternative cryoprotectant in stem cell technology and regenerative medicine due to its ability to withstand extreme cold or desiccation and its biocompatibility. , Recent studies have also identified glycine and betaine as cryoprotective osmolytes, providing nontoxic alternatives to conventional cryoprotecting agents and meeting the increasing demand in modern cell-based medicine .…”
Section: Scope Of Future Applications Of Osmolytesmentioning
confidence: 99%
See 1 more Smart Citation